Factors associated with digital health literacy and attitude towards use of digital health technology among health workers of selected municipalities of Lalitpur district: a mixed method study - Regmi, Amar; Bhandary, Shital (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: Digital health literacy is an individual’s ability to search, understand, and evaluate health information on digital media. There is huge gap in digital health literacy which is rising to create digital gap in context of Nepal which prevents everyone to experiences the advantages of digital health. This study aimed to assess health professionals’ digital health literacy level, attitude towards use of digital health technology and associated factors in two municipalities of Lalitpur district.Method: A Cross-sectional study with a concurrent triangulation mixed-method design was used among thirty-four health professionals working in primary-level health facilities in Lalitpur metropolitan and Mahalaxmi municipality. The duration of study was five weeks (September to October 2023). Variables such as age, education, job type were observed. Bivariate association with chi-square test was done for analysis and identified its associated factor while the thematic analysis was conducted for qualitative data.Result: This study found 24(70.59%) health workers had high digital health literacy while 23(67.65%) had good attitude. Factors such as marital status, job designation, and family monthly income found to be statistically significant with digital health literacy and Job designation, patient served per day, income and access to digital technology were significant with attitude. While triangulating variables such as income and access to digital technology identified as convergent and training, age and education was found to be divergent.Conclusion: Digital health literacy was significantly influenced by technology and recommended to make computers more accessible, offer a training program, and encourage a positive attitude toward this technology.